Construction of a circRNA-miRNA-mRNA Network Related to Macrophage Infiltration in Hepatocellular Carcinoma - Zhou, Peitao; Zheng, Guanglei; Li, Yalin; Wu, Dehua; Chen, Yuhan (Frontiers in Genetics, 2020)
Immune cells in tumor microenvironment play a crucial role in regulating tumor progression. The circular RNA (circRNA) regulatory network involving in immune cell infiltration in hepatocellular carcinoma (HCC) remains largely unknown. In this study, Estimate the Proportion of Immune and Cancer cells (EPIC) application was used to evaluate the fractions of immune cells, cancer associated fibroblasts and endothelial cells of HCC from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. Patients with high macrophage fraction had a better overall survival and macrophage fraction was an independent prognostic factor for HCC. Next, the common differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and circRNAs (DEcircRNAs) between paired tumor and non-tumor tissues were screened out from TCGA and or GEO database. Through spearman correlation analysis, the macrophage-related DEmRNAs were identified to construct a circRNA-miRNA-mRNA regulatory network, which included 6 DEcircRNAs, 7 DEmiRNAs and 45 DEmRNAs. Functional enrichment analysis revealed that these DEmRNAs were mainly involved in immune-related processes. Furthermore, 6 hub DEmRNAs were identified to establish a hub circRNA regulatory network. Among the DEmRNAs in the network, PRC1 was identified as the most influential node. PRC1 high expression was correlated with poor prognosis and low macrophage infiltration of HCC. Taken together, we identified certain circRNA regulatory network related to macrophage infiltration and provided a novel insight into mechanism study and therapeutic targets for HCC.